Unusual clinical presentation and complications following preoperative embolization of a large adrenal tumor - Garg, Puneet; Aggarwal, Ankita; Krishnan, Venkatram; Bajaj, Sunil Kumar; Misra, Ritu Nair (International Journal of Research in Medical Sciences, 2019)
Authors present a case of a young female presenting with secondary amenorrhea which on further investigation revealed a large intra-abdominal mass, likely arising from the left adrenal gland. As the tumor was highly vascular with large feeders, she was referred for pre-operative embolization to reduce the blood loss during surgery. Post embolization, the patient suffered from an unusual complication of tumor rupture along with excessive secretion of catecholamines resulting in myocarditis and myocardial infarction. Patient ultimately died of the myocardial infarction. Preoperative embolization of a large, hypervascular adrenal mass lesion is not devoid of unusual complications like tumor rupture and subsequent cardiovascular complications even if the tumor is hormonally inactive. This complication is extremely rare and has never been reported in adrenal tumors after embolization.